GENDER EFFECT ON FINANCIAL RISK TOLERANCE: THE CASE OF SAUDI ARABIA - Razan Ibrahim Altowairqi; Tahar Tayachi; Uzma Javed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study was done to examine the relationship between gender and financial risk-taking behavior among professionals in Saudi Arabia. Additionally, the study has examined if demographic variables namely, age, income, education and marital status interact with gender to determine differences in risk preferences. This work was done based on quantitative method. Questionnaire based on Grable & Lytton 13-item scale was used for survey data collection. The sample population of this work comprised of 244 professionals in banking and financial sector in Saudi Arabia. An independent sample t-test, chi-square test and two-way ANOVA was used to examine the data obtained. The key outcome of this work has shown that impact of gender on financial risk tolerance was insignificant between professionals in Saudi Arabia. The results also determined that the demographic factors, age, income, education and marital status do not significantly affect financial risk tolerance among genders. This study indicates that understanding risk tolerance is a complex process that goes beyond the exclusive use of demographic factors.